Annex to MS94: Compilation of case study reports A compendium of case study reports from 40 cities in 14 European countries - Cristina Garzillo; Peter Ulrich (WWWforEurope, 2015)
The reports were written by 16 field researchers as the result of the field research conducted in the second half of 2013 in 40 cities in 14 countries across Europe. They explore what institutions are required to ensure a local transition towards sustainability. They synthesise all relevant information for each city, collected by the field researchers throughout their field and the preparatory research, enriching and contextualizing the data collected via questionnaires and face-to-face semi-directed interviews as well as additional desktop research. Thus, they constitute a relevant component for data analysis and interpretation and for answering the research questions of the research project “The Role of Cities in the European Socio-Ecological Transition (ROCSET)”, which is part of the larger WWWforEurope project. The reports are structured into seven sections. In the first part, a general city profile first provides background information, giving factual data on size, population, climate, special characteristics, etc. and providing information on basic government/administrative structure as well as on economic conditions (growth trend, key business and industries, employment, etc.). Then local lifestyle and key challenges and trends (economic, social and environmental ones) are addressed. The second part comprises a sector specific synthesis for water, energy and green spaces, each referring to availability, affordability and consumption levels, key issues, key actors/partnerships and key actions/measures/initiatives. The third part looks into governance and citizens participation, specifically into multilevel governance (province, national, EU) and participation and bottom-up action. In the conclusion, a short summary is provided, and finally trends and challenges for the future are outlined. All reports contain a references section at the end of the document. The compendium covers all selected countries and cities and provides an important insight into each case through the eye of the respective field researcher processing all his/her collected relevant information in it.
Keywords: 330